Separation And Characterization Of The Vanillin Compaund From Soda Lignin. - Mohamad Ibrahim, M.N.; Nor Nadiah, M. Y.; Norliyana, M. S.; Shuib, S (2006)
The separation of vanillin from soda lignin that was extracted from black liquor of oil palm empty fruit bunches (EFB) using 20% sulfuric acid is presented in this paper.